2012
DOI: 10.1088/0004-637x/762/1/55
|View full text |Cite
|
Sign up to set email alerts
|

MOSTSPACE TELESCOPE PHOTOMETRY OF THE 2010 JANUARY TRANSIT OF EXTRASOLAR PLANET HD80606b

Abstract: We present observations of the full January 2010 transit of HD80606b from the Canadian microsatellite, Microvariability and Oscillations of Stars (MOST).By employing a space-based telescope, we monitor the entire transit thus limiting systematic errors that result from ground observations. We determine measurements for the planetary radius (R p = 0.987 ± 0.061R Jup ) and inclination

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A few days after again with Spitzer, Hébrard et al (2011) observed the whole transit of January 2010 with a mid-time accuracy of ±85 seconds. Roberts et al (2013) observed the same transit with the MOST satellite and reached a lower accuracy of ±294 seconds. All the other available observations were made from the ground in February 2009 (Moutou et al 2009;Garcia-Melendo & McCullough 2009;Fossey et al 2009;Hidas et al 2010), June 2009(Winn et al 2009, or January 2010 (Shporer et al 2010) and could only observe partial portions of transits with a given telescope; so their accuracies on the mid-transit times were ±310 seconds or even poorer.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…A few days after again with Spitzer, Hébrard et al (2011) observed the whole transit of January 2010 with a mid-time accuracy of ±85 seconds. Roberts et al (2013) observed the same transit with the MOST satellite and reached a lower accuracy of ±294 seconds. All the other available observations were made from the ground in February 2009 (Moutou et al 2009;Garcia-Melendo & McCullough 2009;Fossey et al 2009;Hidas et al 2010), June 2009(Winn et al 2009, or January 2010 (Shporer et al 2010) and could only observe partial portions of transits with a given telescope; so their accuracies on the mid-transit times were ±310 seconds or even poorer.…”
Section: Conclusion and Discussionmentioning
confidence: 84%
“…Figure 2a shows the relative polarimetric amplitude of a transit versus R p /R * for R p /R * < 0.5 and b = 0. We adopt HD 80606 limb darkening coefficients (Roberts et al 2013, c 1 = 0.742 and c 2 = 0.458), as well as 460 nm solar limb polarization profile coefficients (Faurobert et al 2001, P 1 = 0.87% and k = 70), because limb polarization is difficult to measure for most stars.…”
Section: Scaling With Planet/star Radius Ratiomentioning
confidence: 99%
“…The POLISH2 polarimeter at the Lick Observatory Shane 3-m telescope uses two photoelastic modulators to simultaneously measure Stokes I, Q, U , and V (see Wiktorowicz & Matthews 2008;Wiktorowicz 2009 for the prototype POLISH). Using this system, we obtain B band observations during a transit ingress of HD 80606b (first contact 06:17 UT, February 1, 2013: H10; Shporer et al 2010;Roberts et al 2013). We also obtain 4.9 hours of control data during the previous night to complement the 7.1 hour observation during transit.…”
Section: Observationsmentioning
confidence: 99%